Effectiveness of neurobic exercise program on memory performance in community-dwelling older adults with mild cognitive impairment: A randomized controlled crossover trial - Wiyakarn Sanghuachang; Pornpat Hengudomsub; Nujjaree Chaimongkol; Naiphinich Kotchabhakdi (Belitung Nursing Journal, 2023)
Background: Mild cognitive impairment (MCI) is an early stage of cognitive decline in individuals who are still able to perform their activities of daily living. They are at increased risk of developing dementia. Improving and maintaining cognitive functions are essential goals for older people with MCI to delay or prevent the transition to dementia. Objective: This study investigated the effect of the neurobic exercise program on memory performance among community-dwelling older adults with MCI. Methods: A single-blind, randomized, controlled, two-period crossover design was used. Thirty-two older adults who met the study criteria were randomly assigned to one of two sequence groups, A (n =16) and B (n = 16). Group A received three weeks of neurobic exercise, followed by a three-week washout period, and then three weeks of the traditional brain exercise program. Group B received the treatments in the reverse order but otherwise in a similar manner. Two aspects of memory performance were evaluated: subjective memory and objective memory. Blinded evaluators measured the outcomes four times at baseline, post-intervention (week 3), follow-up stage (week 7), and the end of the study (week 9). Descriptive statistics, independent t-tests, and repeated measures ANOVA were employed for data analyses. Results:  For subjective memory, rmANOVA revealed a significant difference of within-subject (F1.437, 43.113 = 9.324, p <0.05) and interaction effect (time*group) (F1.437, 43.113 = 12.313, p <0.05) and also showed significant differences of within-subject (F1.794,53.811 = 28.931, p < .05) and interaction effect (time*group) (F1.794, 53.811 = 31.190, p <0.05) for objective memory. The study results revealed that the participants in both groups had significantly lower mean scores on the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE), indicating better or improved subjective memory. They also had significantly higher mean scores on the Common Objects Memory Test (COMT) after receiving the neurobic exercise program, indicating improvement in cognitive performance. Conclusion: The neurobic exercise intervention could improve subjective and objective memory among community-dwelling older adults with MCI more than those who received the traditional brain exercise program. Therefore, the neurobic exercise program can be used by the nurse and multidisciplinary teams to enhance memory performance among older adults with MCI.   Trial registration: Thai Clinical Trials Registry (TCTR) 20210326003.